Prevalence and associated factors of constipation among hospitalised adult patients in Hospital Universiti Sains Malaysia - Zaidi, Nurul Izzah Muhamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
It is expected that those with health problems are at risk for constipation due to its many associated factors. Thus, this study aims to assess the prevalence of constipation and its associated factors among hospitalized adult patients. A cross-sectional study was conducted in two medical and two surgical wards, in Hospital Universiti Sains Malaysia from January 2022 to April 2022. A total of 137 adult patients, aged between 18-65 years old and fulfilled the inclusion criteria were randomly selected as the respondents of this study. The data was collected using a self-administered questionnaire and data were analysed with Statistical Package for Social Science (SPSS) version 26.0 windows. Pearson’s Chi Square or Fisher exact test was used to determine the association of selected factors with constipation. The results showed that the prevalence of constipation was 26.3% and most respondents had stool type 1 on Bristol Stool Scale. Only age was found as significantly associated to constipation (p=0.029) in terms of socio-demographics factors. The study also revealed that plain water intake and physical activity were not associated to constipation. Therefore, it can be concluded that constipation is prevalent among hospitalised adult patients in Hospital USM. Thus, there is a need to focus on hospitalised patients so that the preventative measure for constipation can be and avoid of a more severe complications such as chronic constipation among them.